Purchase intention towards alternative medicine: a study from consumers’ perspective in Malaysia - Haque, A. K. M. Ahasanul; Anwar, Naila; Yasmin, Farzana; Kumar Tarofder, Arun; Maziz, Nazmul Mohammad Hassan (Tehran University of Medical Sciences (TUMS) Journals Publishing House, 2020)
Modern medication has proven to be effective in preventing and curing many types of illnesses and prolonging life of many people. However, as mod ern medicines rely on the issuance of synthetic med ications, they produce negative side effects that practically supersedes the advantages that one gains from using them. Therefore, consumers are in search of other types of medications particularly, alternative medicines. I